Gene expression silencing therapy in tumors, focus on gastrointestinal and genitourinary tumors - El-Ghazzi, Nathan; Italiano, Antoine; Angeli, Eurydice (Frontiers in Immunology, 2025)
Precision oncology has seen significant progress with oligonucleotide-based therapies, which provide a novel approach to gene expression silencing. These therapies, including antisense oligonucleotides (ASOs), small interfering RNAs (siRNAs), and microRNAs (miRNAs), target specific genetic sequences with high precision. They offer promising solutions for cancers resistant to conventional treatments due to their ability to modulate previously “undruggable” targets and their reduced toxicity. However, challenges such as susceptibility to degradation, poor cellular uptake, and off-target effects have hindered their clinical application. Advances in chemical modifications and delivery systems, like lipid nanoparticles and GalNAc conjugates, have improved the stability and efficacy of these therapies. This review discusses the structural features, mechanisms of action, and clinical applications of ASOs, siRNAs, and miRNAs, focusing on gastrointestinal and genitourinary cancers. We highlight successful oncology applications, such as siRNA-based therapies targeting specific oncogenes, which have shown promise in clinical trials. Continued advancements in this field are paving the way for more effective and safer cancer treatments.